Perceptions of Feminism on a University Campus. - Jenks, Tracy; Matysik, Allison; Seroogy, Martha; Verriden, Amanda L. (My University, 2009)
The present study was interested in determining how students from the University of Wisconsin-Eau Claire (UWEC) perceive feminism. The researchers conducted structured, face to face interview around the Eau Claire campus with a small sample of college students.
Color poster with text and graphs.
Keywords: Feminism--Public opinion; College students--Attitudes; University of Wisconsin--Eau Claire--Students--Attitudes; Feminism and higher education; Posters